Hubungan Masa Kerja, Usia, Status Gizi, Kecukupan Energi, Kebiasaan Merokok dengan Kelelahan Kerja pada Petani Padi - Antika, Rindi; Prameswari, Galuh Nita (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Work fatigue is defined as a feeling of fatigue and a decrease in alertness that manifests differently for each individual, all of which result in a loss of efficiency, a decrease in work capacity, and a decrease in body resistance. Work fatigue can cause everything from decreased productivity to workplace accidents. Work fatigue can be influenced by a number of factors, including work period, age, nutritional status, energy sufficiency, and smoking habits. Method: The research method used is cross-sectional with a purposive sampling technique. Farmers from Wado village, Kedungtuban district, and Blora district comprise the research sample. Direct interviews (door to door) were used to collect 24-hour recall data and age, as well as the IFRC (Industrial Fatigue Research Committee) questionnaire to collect work fatigue data and anthropometric measurements of weight and height. Univariate and bivariate analysis, as well as the chi-square test, were used to analyze the data. Results: The results showed that there was a significant relationship between work period, age, nutritional status, energy adequacy level, smoking habits on work fatigue in rice farmers in Wado village with p value < 0.05.